Technology Entrepreneurship Project (ENT 600) : Golf GPS Glasses / Mohammad Haikal Mohd Jamil - Mohd Jamil, Mohammad Haikal; Kamarulzaman, Khairilfiqri Syazwan; Habibulah, Hamizan Ahmad; Mushari @ Mashuri, Muhammad Khairun Naim; Mardiman, Muhammad Faiz (2021)
This report is coming from the Technology Entrepreneurship (ENT) subject that we learned. As a student in UiTM Perlis, it is a part of study for everyone to undergo a new product development project. This study learned about the factors that can helped us to launch a new product and get chance to develop and innovate a product that deeply interests us, which is a Golf GPS Glasses. In the first phase, there was a general introduction to the new product development. In this phase, the explanation about the problem of statements, objective and methodologies were explained. Second phase, in the new product development section, the explanations about the product will be explained in this section, which is the product definition, the classification of New Product Development and the process. This development and process of NPD is divided into five parts which is Research and Development, Product Design and Features, Concept Testing, Build Prototype and Test Marketing. In the last phase is a conclusion, the feedback received from respondents was very helpful in order for us to fill up the consumer demands.